PENGARUH LAYANAN INFORMASI DENGAN MEDIA FLIPBOOK DIGITAL DALAM MENGURANGI PERILAKU KONSUMTIF GENERASI Z DI SMK NUR AZIZI TANJUNG MORAWA T.A 2024/2025 - Raziqa Nurul Aulia; Dina Hidayati Hutasuhut; Ika Sandra Dewi; Nur Asyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Consumptive behavior among generation Z, especially vocational high school students, is becoming an increasingly worrying phenomenon along with technological advances and unlimited access to information. This study aims to determine the effect of information services using flipbook media in reducing consumptive behavior of generation Z at SMK Nur Azizi. This study uses a quantitative approach with a pre-experimental method of one group pretest-posttest design. The population in this study were all 120 grade XI students of SMK Nur Azizi, with a sample of 35 students selected by purposive sampling. Data were collected through a validated consumptive behavior questionnaire, both before and after the provision of information services using flipbook media. Data analysis used the t-test (paired sample t-test) with the help of SPSS. The results of the hypothesis test showed that there was a significant difference between the pretest and posttest scores, with a significance value (sig.) 0.000 <0.05. This shows that information services with flipbook media are effective in reducing the level of student consumptive behavior. The conclusion of this study is that the use of flipbook media as a means of information services can be an innovative and educational alternative in guidance and counseling to help students control consumptive behavior. This study provides recommendations for BK teachers to be more creative in using attractive visual media to convey information related to personal financial management.